Epistemologi Anemia dan Upaya Pencegahannya - Noeraini, Vina Aresya; Adam, Arlin (Universitas Pahlawan Tuanku Tambusai, 2025)
The World Health Organization (WHO) shows that the prevalence of anemia occurs as much as 40% in children aged 6-59 months, 37% in pregnant women, and 30% in women aged 15-49 years. The results of the 2018 Basic Health Research report by Balitbangkes show that the prevalence of anemia in the 15-24 age group is 27.2% in adolescent girls. This study examines the epistemological aspects of anemia in adolescents and its prevention efforts from a philosophical perspective through a literature review. The findings show that anemia can be caused by a lack of knowledge and prevention and management efforts. Prevention can be in the form of consuming healthy foods rich in iron, folic acid, vitamin B12, vitamin A, and other nutrients, as well as taking supplements according to the recommendations of health service providers. Prevention of anemia in adolescent girls is very necessary, because the impacts caused by anemia are very complicated, including an unfit body condition, difficulty concentrating, disruption to activity and productivity.